Earning Quality and Firm-Specific Return Volatility –The Case of Pakistan - Aziz, Muhammad Irfan (UW Journal of Management Sciences, 2024)
ABSTRACT Purpose: The study aims is to empirically study the connection between earning quality and firm-specific return volatility. Design and Methodology: The dataset is comprised of 40 manufacturing companies that trade on the KSE 100 index in Pakistan Stock Exchange, covering the period from 2013 to 2022. Multivariate regression is employed to evaluate the impact. Idiosyncratic volatility is used as a proxy of firm-specific return volatility. Idiosyncratic volatility is estimated using the CAPM and Fama French three-factor models. Findings: It has been found that earnings quality and firm-specific return volatility have a significant negative correlation. Keywords: Firm-specific return volatility, earning quality, idiosyncratic volatility